Pijat Oketani Mempengaruhi Produksi ASI pada Ibu Postpartum - Nurfatni Junita; Susaldi; Nurul Fauziah; Putri Dwimeiza Sulistyowati; Siti Hamida Maisaroh Nurlatu; Tazkiyatun Nafs (MPI Press, 2022)
Introduction: The non- smooth milk production can be prevented by one way, namely using the oketani massage method. The advantages of oketani massage are able to overcome problems that are often experienced by nursing mothers, namely dragging milk, mastitis and low milk production. This oketany massage aims to help restore and maintain the natural breast contour and natural breast appearance. The oketani massage method is massage does not cause discomfort or pain to the mother, the mother suddenly feels relieved and comfortable, lactation is increased regardless of the size or shape of the breast and the nipple is repaired and nipple injury and mastitis are prevented. Objectives: This literature search aims to analyze the results of related studies that focus on oketani massage on breast milk production in postpartum mothers. Method: This study is a literature review, to review the effect of oketani massage on breast milk production in postpartum mothers. Sources for conducting literature includesearch studies Google Scholar, Book, E-Journals, by using keywords, namely oketani massage, breast milk production, postpartum. Result: Based on the search of articles that have been analyzed, most of them state that giving oketani massage is effective on milk production, gives mothers a sense of comfort, reduces anxiety in mothers, and makes babies calm when breastfeeding. Conclusion: Giving oketani massage is effective for breast milk production in postpartum mothers.